Continuing Education During Times of War: Experiences of Children in Northern Sri Lanka - Lakshman, Iresha M.; Rajeshkannan, Rajeswaran; Schubert, Mark (European Scientific Journal, ESJ, 2020)
The primary objective of the study was to explore the experiences of children during and after 30 years of civil war with particular attention on its impact on their academic learning. The research intended to answer two research questions, namely 1) How did the war impact on children’s education? and 2) What support networks were available for children affected by war to remain in school and/or to continuously engage in academic learning? The research was carried out in the Jaffna District of Northern Sri Lanka and depended entirely on qualitative data generated through in-depth interviews, key informant interviews, focus groups discussions and observations. Multiple displacements caused by war, the impact of war on livelihoods and the trauma caused by war has resulted in some students losing interest in school and eventually dropping out. In spite of various financial and other support provided by local and international NGOs only some children have remained in school with a sustained interest in education. A characteristic common to these children was that they came from more ‘secure’ family backgrounds. The security offered by intimate relationships within the family seems crucial for educational success even during times of war. The findings suggest the need for strengthening family well-being and stronger emotional support to ensure sustained interest in education during times of war.